155k views
4 votes
Which of these is equivalent to the function g(x) = –|2x + 4| + 3? A g(x) = -(2x + 4) + 3 B g(x) 2x + 7, x < -2 -2x – 1, x > -2 C 9(x) = {-2x – 1, x < -2 2x + 7, x>-2 D g(x) -(2x + 4) + 3, x < 0 (2x + 4) + 3, x-> 0 Education Inc.

User Jsamol
by
4.8k points

1 Answer

3 votes

Step-by-step explanation:

g(x) = –|2x + 4| + 3

|2x + 4| means (2x + 4) or -(2x + 4)

g(x) = (2x + 4) + 3

or g(x) = -(2x + 4) + 3

Solving the first one:

g(x) = (2x + 4) + 3

g(x) = 2x + 4 +3

g(x) = 2x +7

Solving the 2nd one:

g(x) = -(2x + 4) + 3

g(x)

User Dabblernl
by
5.1k points